Economic Convergence Among Urban Areas In North Sumatera - Hutasuhut, Khairul Ali; Siahaan, Lasma Melinda; Hutasuhut, Julianto (Journal of Sustainable Economics, 2025)
This research investigates the convergence of the urban regional economy in North Sumatra from 2018 to 2022, employing a quantitative and descriptive approach to analyze the factors influencing the Regional Gross Domestic Product (GRDP). Data, derived from the Central Statistics Agency (CSA), encompasses eight cities: Sibolga, Tanjungbalai, Pematangsiantar, Tebing Tinggi, Medan, Binjai, Padangsidimpuan, and Gunung Sitoli. The study focuses on three independent variables—population (X1), Human Development Index (HDI) (X2), and Open Unemployment Rate (OUR) (X3)—aiming to understand their simultaneous and partial effects on GRDP. Hypotheses are formulated, indicating the anticipated influence of each variable, with the null hypothesis positing no significant effect. Utilizing eViews version 12 for panel data regression analysis, the results reveal that collectively, Population, HDI, and OUR significantly influence GRDP in the urban regions of North Sumatra. However, when analyzed individually, only HDI and TPT exhibit significant impacts, while Population does not. This suggests that the quality of human development and the unemployment rate play pivotal roles in driving economic convergence. The findings contribute to a nuanced understanding of the convergence dynamics in the cities studied, emphasizing the importance of targeted policies to foster inclusive and sustainable economic growth in the region.